Migration of contaminants associated with pavement construction - Taylor, Jackie V. (2004)
In order to achieve the goals of 'Sustainable Development', alternative (secondary) materials are being increasingly used as bulk-fill aggregate within pavement construction as substitutes for traditional aggregates. This finds an end-use for stockpiles of industrial by-products (and hence the allowing the land on which they stand to be reclaimed for other uses) and protects finite, natural resources which they replace from over-extraction.